2018
DOI: 10.22434/ifamr2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of farm success factors by commercial farm managers

Abstract: This study elicits U.S. agricultural producer preferences for five key management success factors: managing output prices; managing production; controlling costs; managing land/equipment/facilities; and managing people. The objective of this analysis was to determine the relative importance of each of the five profit-centric functional areas of management among U.S. farm managers. Significant heterogeneity in preferences was observed over the management areas. Farm managers, on average, placed the highest impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…However, employee management seems to be a major contributor to class 3—“Human Hurdles”—membership of the LCM. For example, producers who ranked managing people as the most important management factor on their farm are more likely to be in class 3—“Human Hurdles”—than class 1—“Traditional Production Risks.” This result is consistent with recent research that found managing people plays an important role in determining farm business success (Lai et al., ). In particular, Lai et al.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, employee management seems to be a major contributor to class 3—“Human Hurdles”—membership of the LCM. For example, producers who ranked managing people as the most important management factor on their farm are more likely to be in class 3—“Human Hurdles”—than class 1—“Traditional Production Risks.” This result is consistent with recent research that found managing people plays an important role in determining farm business success (Lai et al., ). In particular, Lai et al.…”
Section: Resultssupporting
confidence: 93%
“…In particular, Lai et al. () found that larger operations, in terms of gross farm sales, placed more emphasis on managing people, which is consistent with the expectation of increasing complexity associated with larger operations (Bitsch & Olynk, ; Greiner, ). Although our ex post analysis of demographic characteristics fails to support any relationship between the farmer perceptions of human risk and gross farm sales (Table ), we do find that mean enterprise sizes for a variety of enterprises are largest for respondents most likely to be in class 3—“Human Hurdles—including milking dairy cows and fed dairy heifers, feeder pigs, and corn and soybean acres (Table ).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The importance of key management factors in the success of farm businesses has previously received research attention (Holland et al, 2014;Lai et al, 2018), but these studies did not consider the similarities and differences between management strategies based on farmers' primary production activity. Holland et al (2014) used choice-based data from the 2013 edition of the Large Commercial Producer Survey to identify the most important predetermined management factors as controlling costs and managing production.…”
Section: Introductionmentioning
confidence: 99%